PREDIKSI SEDIMEN DI WADUK SERMO DARI SUB DAS NGRANCAH KABUPATEN KULONPROGO - , MUSTIKA SARI; , Prof. Dr. Ir. Putu Sudira, MSc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ngrancah Sub Watershed is a Watershed located above Sermo Reservoir, Kulonprogo Regency. The Sermo Reservoir utilized as a source of water by the Regional Water Company (PDAM) and also iirigation water to irrigate rice fields in the surrounding area and Wates District. However, basically the availability of water in Sermo Reservoir from year to year is declining. This happens because of the environmental damage cause erosion, and then the result of erosion as sediment is being accumulated in the river. The more sediments transported and settled in reservoir causing siltation and can reduce the age of reservoir. This research aims of predicting discharge using Mock methods and predict sediment into the Sermo Reservoir from Ngrancah River In this research, the sediment was calculated using the method of Meyer-Peter and Muller's. Ngrancah Sub Watershed model parameters are sub-watershed area = 20.56 km2, infiltration coefficients wet season (WIC) = 0.67, coefficient of infiltration dry season (DIC) = 0.78, initial soil moisture (ISM) = 100 mm, soil moisture capacity (SMC) = 170 mm, initial groundwater storage (IGWS) = 700 mm and groundwater recession constanti (K) = 0.49 . The prediction of sediment transported to the Sermo Reservoir for 10 years (2002-2011) amounted to 5,579,927.18 m3.